The Use of Google Earth Media in IPAS Learning to Develop Elementary School Students’ Spatial Abilities - Emil Hardiansyah; Ilham Saleh; Hasrul H; Suwandi Lausu; Indra Jaya Kusuma (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examined the effect of using Google Earth as an instructional medium on elementary students’ spatial ability in IPAS (Integrated Science and Social Studies) learning focused on spatial concepts. A quantitative quasi-experimental method with a nonequivalent control group pretest–posttest design was employed. The sample comprised 52 sixth-grade students: an experimental class from SD Negeri 4 Palu (n=29) and a control class from SD Negeri 20 Palu (n=23). The intervention lasted four sessions using structured exploration activities with Google Earth supported by worksheets, while the control group learned with conventional media (static maps/pictures). Spatial ability was measured using a 35-item test (25 multiple-choice and 10 open-ended items) converted to a 0–100 scale. Data were analyzed descriptively, followed by gain/N-gain computation, an independent-samples t test at α=0.05, and effect size estimation using Cohen’s d. Results indicated a significant difference in improvement between groups (p = 0.000019) with a large effect (Cohen’s d = 1.20). The largest gains were observed in distance–direction–location relations and 2D–3D transformation skills. These findings suggest that Google Earth is an effective interactive visual medium to enhance elementary students’ spatial understanding in IPAS learning